Innovations in fuel cell technologies - Steinberger-Wilckens, Robert; Lehnert, Werner (Royal Society of Chemistry, 2010)
"This book reviews the state-of-the-art in fuel cells (low and high temperature) across all the types applied in the field today and assesses current trends in development. The main technology problems are discussed and current gaps to market success identified. The innovations covered in the book deliver new answers to pertinent problems and/or offer new opportunities, be it in operating conditions, application area, extension of lifetime, new fuels, exciting new diagnosis and analysis methods. The volume gives an insight not only to the key developments within the next few years, but also shows perspectives in the mid-term."--Publisher.
Keywords: Fuel cells.; elektronické knihy; electronic books